Photonic switching and interconnects - Marrakchi, Abdellatif (Optical engineering (Marcel Dekker, Inc.), 1994)
This volume offers state-of-the-art research on photonic switching and interconnects, describing a variety of systems used in optical telecommunications and computer networking and analyzing the performance of many optical components used in these systems. The book examines a host of optical components, including integrated optical switches, arrays of surface-emitting lasers, two-dimensional spatial light modulators, microlenses and self-electro-optic effect devices.